Diketopyrrolopyrrole and perylene diimine-based large π-molecules constructed via C–H direct arylation. (August 2022) - Wang, Li-Hong; Liu, Li-Lin; Liu, Hui; Chen, Yan; Ye, Dong-Nai; Fu, Weifei; Liu, Shi-Yong
Abstract: Diketopyrrolopyrrole (DPP) and perylene diimine (PDI) dye moieties with unique structure and strong light absorption have been widely explored as building blocks for organic opto-electronic materials. In this work, we implement a proof-of-concept of welding DPP and PDI together as propellers for the design of novel molecules with star-shaped or three-dimensional (3D) geometries and minimized self-aggregation. Three large conjugated molecules Ph(DPP-PDI)3, Py(DPP-PDI)4 and SF(DPP-PDI)4 with different central cores, i.e., benzene, pyrene and spirofluorene, are designed and facilely synthesized via atom- and step-economic C–H direct arylation (DACH) coupling. The optical, electrochemical properties and photovoltaic performance of target molecules with varied geometries, are systematically investigated by UV–vis absorption, cyclic voltammetry and bulk heterojunction devices, which reveal that 3D molecules have a broader light absorption, much higher extinction coefficients and more favorable energy levels compared with mono DPP-PDI precursor. Our study demonstrates that DACH reaction is an effective and extensible method to prepare branched or 3D π-electronic materials, and provides a guideline for the rational design and synthesis of complex π-molecules in a simple way. Graphical abstract: Image 1 Highlights: DPP and PDI, as two bright dyes, are bound together for the first time to construct star-shaped or 3D conjugated molecules. C–H direct arylation is demonstrated as an extremely efficient synthetic strategy toward branched π-functional molecules. Structure-property-performance correlations going with the evolution from π-subunits to large target molecules are studied. Pyrene-cored star-shaped tetramer Py(DPP-PDI)4 display highest photovoltaic performance among all target molecules.